(untitled) (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: The suprasellar region of the brain, which contains critical structures, is susceptible to various pathological processes, leading to significant diagnostic and therapeutic challenges. Accurate evaluation of suprasellar masses is essential for effective patient management. This study aimed to evaluate the consistency and diagnostic accuracy of computed tomography (CT) imaging compared to histopathological findings in patients with suprasellar masses. Methods: Conducted between July 2004 and June 2005 at Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, this study included 60 patients with suprasellar masses who underwent preoperative CT scans with thin slices (1.5–3 mm) followed by histopathological analysis of biopsy materials taken from the resected suprasellar masses. The histological study of the excised suprasellar masses was done to establish a diagnosis, classify its type, and compare the same with its CT diagnosis to decide whether CT scan can fairly diagnose and classify types of suprasellar masses. Results: The patient population predominantly included young and early middle-aged individuals, with a mean age of 30.2 years (range: 7 – 55 years). Notably, CT scans identified pituitary macroadenomas in 60% of cases, while histopathology confirmed this in 51%. The diagnostic results for craniopharyngiomas were consistent across both modalities. The comparison of diagnoses between CT and histopathology revealed comparable outcomes for various suprasellar masses, with an insignificant Chi-square result (p = 0.818), suggesting a consistent diagnostic capacity. Conclusions: While CT imaging provides valuable initial insights into suprasellar masses, histopathology remains the gold standard for definitive diagnosis. This study highlights the importance of combining both diagnostic modalities to enhance accuracy and improve management strategies for patients with suprasellar masses. Future research should focus on optimizing imaging techniques and exploring additional biomarkers to further refine the diagnostic process. Ibrahim Card Med J 2024; 14(1): 67-71